Before the storm - Shipman, James D. (Kensington Publishing Corp., 2023)
In 1948 Berlin, Sara Sturm, a German woman working for the U.S. Department of Public Affairs, is dispatched to investigate a store vandalized with swastikas and helps two Jewish Holocaust survivors track down a Nazi nuclear scientist whose knowledge may determine the course of countless wars to come.